COMPARISON OF POISSON, ZIP, ZINB, HURDLE AND ZIGP REGRESSION ANALYSIS METHODS IN SCHOOL-AGED SMOKING CASE MODELING IN KUDUS DISTRICT, CENTRAL JAVA - Elok Fitriani Rafikasari; Suci Ismadyaliana; Dwilaksana Abdullah Rasyid; Setiawan Setiawan (Bajang Institute, 2021)
Smoking behavior among adolescents and children, especially boys, is increasing from time to time. This is very unfortunate considering the many harmful substances in cigarettes that can interfere with health. Modeling related to smoking cases for adolescents and school-age children is needed as a step to anticipate and deal with this problem. In this study we use the Poisson, ZIP, ZINB, Hurdle, and ZIGP regression methods to modeling the number of cigarettes consumed by adolescents and boys. The best model selection is done by the Vuong test. The results showed that the most suitable model was ZIGP with variables that had a significant effect on the amount of cigarette consumption in adolescents and children are age and education level